APPLYING HELLOTALK AND TANDEM IN TEACHING SPEECH ACTS TO UZBEK B2 LEVEL LEARNERS IN INDEPENDENT EDUCATION (International journal of artificial intelligence, 2025)
This study explores the effectiveness of using HelloTalk and Tandem in teaching speech acts to Uzbek B2-level learners in independent education. With the rise of digital language learning tools, mobile-assisted language learning (MALL) applications provide learners with immersive and interactive environments. This paper investigates how these applications can enhance pragmatic competence in speech acts, including requests, apologies, refusals, and compliments. The findings suggest that both applications contribute to learners' ability to use speech acts appropriately in diverse communicative contexts.